The Effect of Professionalism and Structural Empowerment on Job Satisfaction of Inpatient Nurse - Rita Yuliana Sari; Kuswantoro Rusca Putra; Nurul Muslihah (Universitas Aisyah Pringsewu, 2023)
Nurses are one of the health workers who provide primary health services. Apart from being a large number in hospitals, its presence and role are strongly associated with patient safety and quality of care. Nurse job satisfaction has become one of the benchmarks for the quality of patient care. Research on the effects of professionalism and structural empowerment simultaneously on job satisfaction has never been done before. This study examines the impact of professionalism and structural empowerment on job satisfaction among inpatient nurses. This study is in the form of a cross-sectional survey. As many as 129 nurses from Bengkayang Regional Hospital and Landak Regional Hospital participated in this study. To collect data, Hall Professionalism Scale, Conditions for Work Effectiveness Questionnaire II, and Job Satisfaction Survey were delivered to respondents. Data were then analyzed using multiple linear regression. According to analysis, there is a significant effect of professionalism and structural empowerment on the job satisfaction of inpatient nurses.Abstrak: Perawat adalah salah sat dari tenaga Kesehatan yang menyediakan pelayanan kesehatan pertama. Selain dari jumlahnya yang besar di rumah sakit, keberadaan dan perannya juga sangat berkaitan dengan keamanan pasien dan kualitas pelayanan. Kepuasan kerja perawat telah menjadi salah satu tolak ukur dari kualitas pelayanan. Penelitian terhadap pengaruh profesionalisme dan pemberdayaan struktural terhadap kepuasan kerja belum pernah dilakukan sebelumnya. Penelitian ini berupaya untuk menjelaskan pengaruh profesionalisme dan pemberdayaan struktural terhadap kepuasan kerja perawat rawat inap. Penelitian ini berbentuk survey cross-sectional. Sebanyak 129 perawat dari Rumah Sakit Daerah Kabupaten Bengkayang dan Rumah Sakit Daerah Kabupaten Landak berpartisipasi di dalam penelitian. Untuk mengumpulkan data, kuisioner Hall Professionalism Scale, Conditions for Work Effectiveness Questionnaire II, and Job Satisfaction Survey diberikan kepada responden. Data kemudian dianalisis menggunakan regresi linier berganda. Berdasarkan hasil analisis tersebut, terdapat pengaruh signifikan profesionalisme dan pemberdayaan struktural secara simultan terhadap kepuasan kerja perawat rawat inap.